Acanthopanax trifoliatus (L.) Merr polysaccharides ameliorates hyperglycemia by regulating hepatic glycogen metabolism in type 2 diabetic mice - Lin, Yuzi; Pan, Jinghua; Liu, Yue; Yang, Huiwen; Wu, Guoyu; Pan, Yufang (Frontiers in Nutrition, 2023)
Drug monotherapy was inadequate in controlling blood glucose levels and other comorbidities. An agent that selectively tunes multiple targets was regarded as a new therapeutic strategy for type 2 diabetes. Acanthopanax trifoliatus (L.) Merr polysaccharide (ATMP) is a bio-macromolecule isolated from Acanthopanax trifoliatus (L.) Merr and has therapeutic potential for diabetes management due to its anti-hyperglycemia activity. In this study, we found that ATMP could effectively improve glucose tolerance and alleviate insulin resistance by promoting insulin secretion and inhibiting glucagon secretion. In addition, ATMP decreases glycogen synthesis by inhibiting PI3K/Akt/GSK3β signaling, reduces glycogenolysis via suppressing cAMP/PKA signaling, and suppresses liver gluconeogenesis by activating AMPK signaling. Therefore, ATMP has the potential to be developed as a new multi-targets therapeutics for type 2 diabetes.